Repositioning of Tamoxifen in Surface-Modified Nanocapsules as a Promising Oral Treatment for Visceral Leishmaniasis - Débora Faria Silva; Levi Eduardo Soares Reis; Marina Guimarães Carvalho Machado; Douglas Daniel Dophine; Vinicius Roberto de Andrade; Wanderson Geraldo de Lima; Margareth Spangler Andrade; José Mário Carneiro Vilela; Alexandre Barbosa Reis; Gwenaelle Pound-Lana; Simone Aparecida Rezende; Vanessa Carla Furtado Mosqueira (Pharmaceutics, 2021)
Standards of care for human visceral leishmaniasis (VL) are based on drugs used parenterally, and oral treatment options are urgently needed. In the present study, a repurposing strategy was used associating tamoxifen (TMX) with polyethylene glycol-block-polylactide nanocapsules (NC) and its anti-leishmanial efficacy was reported in vivo. Stable surface modified-NC (5 mg/mL of TMX) exhibited 200 nm in size, +42 mV of zeta potential, and 98% encapsulation efficiency. Atomic force microscopy evidenced core-shell-NC. Treatment with TMX-NC reduced parasite-DNA quantified in liver and spleen compared to free-TMX; and provided a similar reduction of parasite burden compared with meglumine antimoniate in mice and hamster models. Image-guided biodistribution showed accumulation of NC in liver and spleen after 30 min post-administration. TMX-NC reduced the number of liver granulomas and restored the aspect of capsules and trabeculae in the spleen of infected animals. TMX-NC was tested for the first time against VL models, indicating a promising formulation for oral treatment.